Pengaruh Analisis Jabatan Terhadap Penyusunan Struktur Organisasi (Literature Review) - Annisa Darmaji Putri; Hanifa Putri Wardhani; Netty Merdiaty (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Job analysis is an essential component of developing an effective organizational structure. A systematic process known as “job analysis” is used to determine the responsibilities, authorities, and competencies required for each job position. This analysis helps organizations create a clear structure, prevent overlapping roles, and ensure that jobs are designed to support strategic objectives. This research conducted a literature study by looking at ten articles in relevant journals that included research objectives, results, and suggestions. To facilitate the presentation of the results, the data collected was analyzed and summarized in tabular form. The results show that job analysis is helpful in building an organizational structure that is flexible, efficient, and relevant to business needs. A structure based on job analysis can also improve efficiency, productivity, communication, and employee motivation as well as help organizations adjust to market and technological developments. Based on these findings, organizations are advised to implement job analysis on a regular basis.